Knowledge of Gout and Gout Medication Use among Patients at A Community Pharmacy - Vina Widiastuti; Truly Anggraini (Indonesian Journal of Global Health Research, 2026)
Gout is a common metabolic disorder associated with hyperuricemia, recurrent joint pain, and reduced quality of life. In community pharmacies, patients often obtain gout medicines without adequate understanding of the disease and its pharmacotherapy. This study aimed to describe patient knowledge regarding gout and gout medication use at Ngimbrang Pharmacy, Temanggung, Indonesia. A prospective descriptive study was conducted from 1 March to 23 April 2025 using purposive sampling. A literature-based questionnaire was tested in 30 respondents and demonstrated 14 valid items with good reliability (Cronbach's alpha = 0.776). Data from 54 respondents were analyzed descriptively. Most respondents were male (54.0%), aged ≥60 years (31.0%), and worked as farmers (48.1%). Overall, 46.0% had sufficient knowledge, 41.0% had good knowledge, and 13.0% had poor knowledge. Misconceptions remained regarding alcohol, allopurinol, and diclofenac. Patient knowledge was generally moderate.